THE EFFECT OF PROBLEM-BASED LEARNING MODEL TOWARDS STUDENTS’ COMPREHENSION OF THE ENGLISH READING TEXT - Iskandar Rosyidin; Nurrudin Nurrudin; Ratna Dewanti (University of Kuningan, 2022)
This research entitles The Effect of Problem-Based Learning Model (PBL) on the Students’ comprehension of the English Reading Text. It is aimed at finding out the differences in students’ comprehension of English reading text using the PBL and the TBL models. The methodology used was an experimental method in which there were two groups available. The first group was an experimental group that was treated using the PBL model and the second group was a control group that was treated using the TBL model. The learning models were applied to find out the one which had the greatest effect on the students’ achievement in English reading comprehension. Since the subject delivered was Reading IV, the sampling technique used was purposive sampling, the sample chosen was students of semester IV, English Department of State Polytechnics of Sriwijaya. Based on the result of two-way analysis of variance or ANOVA AB on the level of significance of α = 0,05, it is found that Fhitung = 4,555 dan Ftabel (0,05;1:40) = 4,08. Based on the value of Significance on the table of Tests of Between-Subjects Effects on line A that if it is less than 0.05, the result of the test is significant. In the table of 4.12, the Sig value for line A was 0.039, less than 0.05. Then it is concluded that students treated using the PBL model were far higher in English reading text comprehension compared to those who were treated using the TBL model.